Navigating the AI Frontier in Health Communication Research: Exclusive Interview with Prof. Xiaoquan Zhao, Editor-in-Chief of Health Communication - Jiang, Yueliang; Pu, Siyu; Liu, Haoyi (The Journal of Medicine, Humanity and Media, 2025)
As AI reshapes health communication—from digital likeness impersonating real humans to algorithms predicting epidemics—how can health communication researchers continue to promote and safeguard health as a quintessential human value? On July 6th, 2025, during the MHM2025 conference, we interviewed Prof. Xiaoquan Zhao, Editor-in-Chief of Health Communication. Drawing on more than 20 years of experience as a health communication scholar, Prof. Zhao offers an answer: We should strive to be rational brokers of knowledge amid the technological frenzy and keep humanity at the heart of innovation. In this exclusive interview, he reflects on the evolving role of health communication in the AI age and how academic research can adapt in a rapidly changing world.